Near-orientation deformation banding formation mechanism of Al-Mg-Mn-Er alloy - Hongfu Yang; Mengnie Li; Yaru Wu; Shumeng Lu; Rensong Huang; Shanju Zheng; Xiaohong Yuan; Yonghua Duan (Materials Research Letters)
Near-orientation deformation bands (DBs) are formed through lattice rotation and corresponding dislocation slip. DBs exhibit a strong dependence on orientation. The orientation dependence is closely related to the interaction between the primary and secondary slip systems facilitated by crystal rotation. When two related slip systems are activated and intersect, lattice rotation occurs, and the orientation deviation of the grains gradually increases, resulting in grain splitting and forming a banded structure. This mechanism provides a preliminary theory for regulating Σ3 grain boundaries and introduces a novel method to enhance the performance of aluminum alloys.